TEACHER STRATEGIES IN IMPROVING STUDENT LEARNING MOTIVATION THROUGH ICE BREAKING AT SDN 081 PANYABUNGAN - Ananda Aulia Putri Nasution; Dinda Dwi Puspita; Hotmarito Harahap; Khoirul Ardi Nst (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study aims to describe teacher strategies for increasing student learning motivation through the implementation of icebreakers in learning at SDN 081 Panyabungan. This study used a qualitative approach with a descriptive research style. The research subjects included classroom teachers and elementary school students. Data collection techniques included observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of techniques and sources. The results showed that teachers implemented icebreakers in a planned manner at the beginning, middle, and end of lessons, with short durations and a variety of activities tailored to student characteristics. The types of icebreakers used included enthusiastic applause, short movement-based games, educational songs, and light quizzes. Teacher strategies in implementing icebreakers were proven to create a pleasant learning atmosphere, increase focus, and encourage active student participation. The impact of icebreaker implementation was seen in increased student motivation and active participation in the learning process. Thus, icebreakers can be recommended as an effective learning strategy for increasing student motivation in elementary schools.